The Relationship Between Islam and the State in the Qur'an: Sayyid Qutb’s Perspective on Islamic Political Governance - Syukron, Ahmad; Safei, Abdullah; Satiri, Iwan; Taqwa, Muhammad Irawan (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
This article examines the relationship between Islam and the state from the perspective of Sayyid Qutb, with a focus on his interpretation of political governance in Islam. Sayyid Qutb is renowned for advocating a symbiotic theory, which posits that religion and the state are mutually dependent. In this framework, Islam requires the support of the state to effectively implement its teachings, while the state needs Islam to provide moral and ethical guidance. Qutb’s perspective serves as a middle path between two opposing paradigms: the integralist approach, which fully merges religion and politics, and the secularist approach, which entirely separates them. His ideas have significantly influenced both modernist and neo-modernist movements within Islamic political thought. By analyzing Qutb’s writings and interpretations, this study underscores the continuing relevance of his ideas in contemporary debates on the role of Islam in governance. The findings suggest that his symbiotic model provides a compelling framework for understanding the dynamic interaction between religion and politics in Islamic societies. Practically, this research offers insights for policymakers and scholars regarding the integration of Islamic values into modern governance systems. Future studies could further explore the implications of this paradigm across diverse sociopolitical contexts, particularly in Muslim-majority countries.